1994
DOI: 10.1099/13500872-140-5-1109
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the glycopeptidolipid antigens of Mycobacterium abscessus and Mycobacterium chelonae and possible chemical basis of the serological cross-reactions in the Mycobacterium fortuitum complex

Abstract: Mycobacterium abscessus and Mycobacterium chelonae, two members of the Mycobacterium fortuitum complex, contain five major glycolipids. A combination of NMR spectroscopy, fast atom bombardment mass spectrometry and chemical degradation was used to elucidate their structures. All the compounds belong to the family of glycopeptidolipids. A 6-deoxy-a-~-talosyl unit, which may bear one or two acetyl groups, invariably occupies the site of glycosylation on the threonine residue in the various compounds. A 3,4-di-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…6). However, it is reported that M. fortuitum complex produced GPLs which are glycosylated as in GPL-5 and GPL-6 as major components (19,20). Therefore, these observations suggest that this type of glycosylation is not specific for M. smegmatis.…”
Section: Discussionmentioning
confidence: 48%
“…6). However, it is reported that M. fortuitum complex produced GPLs which are glycosylated as in GPL-5 and GPL-6 as major components (19,20). Therefore, these observations suggest that this type of glycosylation is not specific for M. smegmatis.…”
Section: Discussionmentioning
confidence: 48%
“…The precise nature of these GPLlike compounds was resolved by matrix-assisted laser desorption ionization-time-of-flight mass spectrometry. All of the GPL-associated pseudomolecular ions ([M ϩ Na] ϩ ) detected in the smooth strains perfectly matched the GPLs previously described for M. abscessus in calculated molecular weight (16). In contrast, these GPL-associated pseudomolecular ions were nondetectable in the rough strains (data not shown).…”
mentioning
confidence: 54%
“…3b, square bracket). The colour and mobility of the extra lipids are similar to those of apolar GPLs of M. avium (McNeil et al, 1989), and it has been reported that M. abscessus expresses GPLs (Lopez-Marin et al, 1994). To provide further evidence that these lipids are M. abscessus GPLs, the plates were sprayed with 1-naphthol to detect deoxyhexoses found in GPLs, and extracts were also subjected to mild alkaline methanolysis to which GPLs are resistant (McNeil et al, 1989;Torrelles et al, 2002).…”
Section: Detection Of a Rough Revertant (390v) From M Abscessus 390smentioning
confidence: 90%
“…GPLs are found in the outermost portion of the mycobacterial cell envelope of NTM (Barrow et al, 1980;Furuchi & Tokunaga, 1972;Goren et al, 1972;Ortalo-Magne et al, 1996) and contain antigenic determinants for a number of mycobacterial species (Brennan & Goren, 1979;Camphausen et al, 1985;Lopez-Marin et al, 1994). The GPL molecule typically consists of a tripeptide-amino alcohol core with an amide linked long chain fatty acid.…”
Section: Discussionmentioning
confidence: 99%